(untitled) (Comparative & International Education Series, 2022)
I am a student from Mexico. My area of training is education and I hold a master’s degree in International Higher Education. My interest in this subject arose precisely from an exchange experience I had in Spain in 2016, because after it, I was interested in learning more about the process at the institutional level and the individual experiences of students. Additionally, during this, I was able to meet people from different backgrounds and eliminate some stereotypes and beliefs I had about other cultures.